VD_FINDINFO HC / 2017 / 826 vom 3. Oktober 2017 - VD Tribunal cantonal (2017)
COMPÉTENCE RATIONE LOCI, PROROGATION DE COMPÉTENCE, FARDEAU DE LA PREUVE | 9 LFors, 308 al. 1 let. a CPC (CH), 406 CPC (CH)